2019
DOI: 10.1530/eje-19-0047
|View full text |Cite
|
Sign up to set email alerts
|

Renal impairment is closely associated with plasma aldosterone concentration in patients with primary aldosteronism

Abstract: Objective Several clinical studies have reported that renal impairments are sometimes observed in patients with primary aldosteronism (PA). We analyzed the prevalence of renal impairments in PA patients and identified parameters that increase the risk for them. Design This is a retrospective cross-sectional study. We assessed the PA database established by the multicenter Japan PA study (JPAS). Data were also collected from patients with essential hypertension (EHT). Methods We compared the prevalences of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 29 publications
2
27
0
Order By: Relevance
“…Primary aldosteronism (PA), characterized by autonomous aldosterone production, is a common cause of secondary hypertension, with an estimated prevalence of approximately 10% among hypertensive patients 1‐4 . Previous reports indicate that, due to the effects of excessive aldosterone, renal complications occur more frequently in patients with PA than in patients with essential hypertension (EH) 5,6 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Primary aldosteronism (PA), characterized by autonomous aldosterone production, is a common cause of secondary hypertension, with an estimated prevalence of approximately 10% among hypertensive patients 1‐4 . Previous reports indicate that, due to the effects of excessive aldosterone, renal complications occur more frequently in patients with PA than in patients with essential hypertension (EH) 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…From a clinical perspective, some studies have demonstrated associations between aldosterone level and glomerular filtration rate decline. For example, Kawashima et al demonstrated that plasma aldosterone levels closely associate with renal impairment in patients with PA 6 . Reincke et al showed that markers of disease activity, such as plasma aldosterone and serum potassium, independently predicted low GFR in untreated PA 11 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with patients with essential hypertension, patients with PA have an independent association with higher risks of cerebro-and cardiovascular complications (e.g., stroke, cardiac hypertrophy, atrial fibrillation, coronary artery disease, and cardiac failure), metabolic disturbances, and renal insufficiency [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%